Nitrogen per unit leaf area affects the upper asymptote of Puccinia striiformis f.sp. tritici epidemics in winter wheat - Neumann, S.; Paveley, N.D.; Beed, Fenton D.; Sylvester-Bradley, Rosemary (Wiley, 2004)
Field trials tested which components of epidemic development of Puccinia striiformis, the cause of yellow rust, were affected by nitrogen (N) fertilizer applied to winter wheat. Both timing and amount of N were varied to affect canopy size and leaf N content, and to provide a supply of mobile N to the pathogen, by causing fresh N uptake after leaf expansion was complete. No N was applied to control plots. A logistic disease-progress function was fitted to disease-severity data, which were assessed in absolute units. Leaf area and specific leaf N (g N per m2 leaf tissue) were quantified. Large and highly significant effects of N on the upper asymptotes, or ‘carrying capacities' (c) were found. Effects on rates and points of inflection of the epidemics were not significant. Early N resulted in larger shoot numbers and leaf area, but disease was also more severe, so that by grain filling, the remaining green leaf areas were larger without N than with N. Later N treatments did not increase canopy size, but did increase symptom area compared with the control. These effects differ from the concept that N affects disease as a result of its effect on canopy growth, and therefore canopy microclimate, and suggest instead a substrate effect. Linear regression revealed that 51% of the observed differences in c were explained by variation in specific leaf N, suggesting that growth of the rust fungus may depend directly on particular components of total leaf N.